2010
DOI: 10.1111/j.1365-2036.2010.04378.x
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical trial: the incidence of NSAID‐associated endoscopic gastric ulcers in patients treated with PN 400 (naproxen plus esomeprazole magnesium) vs. enteric‐coated naproxen alone

Abstract: SUMMARY BackgroundGastroprotective co-therapy may reduce the risk of nonsteroidal anti-inflammatory drug (NSAID)-associated gastric ulcers, but adherence is suboptimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 41 publications
4
54
0
7
Order By: Relevance
“…Up to 1 year of dosing with the combination product was completed by patients in the phase 3, US multicenter, double-blind studies and the extension study. These studies, and others with a naproxen/esomeprazole combination, indicate that the relative decrease in endoscopic damage is similar to that found with celecoxib (relative risk reduction of 40% to 50%) 30,31,34,35 . Over the 1-year analysis, the incidence of AEs, AEs leading to discontinuation, and SAEs were similar between the ibuprofen/famotidine and the ibuprofen group with TEAEs reported more frequently among the ibuprofen group.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Up to 1 year of dosing with the combination product was completed by patients in the phase 3, US multicenter, double-blind studies and the extension study. These studies, and others with a naproxen/esomeprazole combination, indicate that the relative decrease in endoscopic damage is similar to that found with celecoxib (relative risk reduction of 40% to 50%) 30,31,34,35 . Over the 1-year analysis, the incidence of AEs, AEs leading to discontinuation, and SAEs were similar between the ibuprofen/famotidine and the ibuprofen group with TEAEs reported more frequently among the ibuprofen group.…”
Section: Discussionsupporting
confidence: 50%
“…Goldstein and colleagues 34 enrolled subjects in two randomized, double-blind, parallel-group, controlled, multicenter studies comparing a fixed combination of 20 mg omeprazole and 500 mg naproxen to 500 mg naproxen alone for 6 months. In these two naproxen studies, the reported premature discontinuation rate was 6.9% and 10.5% for the combination therapy group and 15.7% and 18.1% for the naproxen only group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 selective inhibitors were associated with a lower risk of peptic ulcers and UGIB than non-selective NSAIDs in taking with LDA [141,142], whereas in patients at high risk for recurrence of gastric ulcer taking with NSAIDs plus LDA, use of cotherapy with misoprostol or lansoprazole significantly lowered the risk for gastric ulcer recurrence [110]. Then, in LDA users, naproxen plus esomeprazole was associated with a lower combined incidence of gastric ulcers compared to naproxen [143]. Moreover, in patients with taking LDA, the use of celecoxib or naproxen plus lansoprazole resulted in similar rates of gastroduodenal ulceration [144].…”
Section: Commentmentioning
confidence: 99%
“…Older age is a major risk factor for these adverse experiences [1,11,12], and in particular age ‡60 years [1,4,9]. Previous studies have shown that a large proportion of elderly patients experienced GI nuisance adverse events associated with NSAIDs [1,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Non-steroidal anti-inflammatory drugs (NSAIDs) are a commonly prescribed class for the treatment of pain within this age group, yet chronic use of NSAIDs is known to pose potential cardiovascular and gastrointestinal (GI) risk and may result in non-adherence to NSAID therapy [1,4,9,10]. Older age is a major risk factor for these adverse experiences [1,11,12], and in particular age ‡60 years [1,4,9].…”
Section: Introductionmentioning
confidence: 99%